Quando a mídia vira escândalo: a cobertura dos casos Alceni Guerra e Ibsen Pinheiro (1991-1993) - Elegancia, Edgar Ednadygarra Leite (2013)
This dissertation has as object of study the coverage of printed newspapers Correio Braziliense, Folha de S. Paulo and O Estado de S. Paulo, Veja magazine, about the political scandals that occurred in the early 1990. The first, in 1991, against the then Health Minister, Alceni Guerra, managing President Fernando Collor and the second against the federal representative Ibsen Pinheiro, in 1993. The work seeks to verify the behavior of these media and what the trend in toppings. In these episodes, the politicians in question carried by the press the corrupt rating and had their reputations shattered